Studi Eksperimental Pengaturan Waktu Pengapian Pada Mesin 4 Langkah 1 Silinder Berbahan Bakar E25 - Aji, Arjuna; Triyono, Joko (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2017)
The use of ethanol as a mixture of premium is for reducing dependency to the primuim, considering that premium is not renewable. The goal of the ethanol addition in a fuel is to increase the octane number. However the heating value of the ethanol is lower than premium, so it will decrease the performance of the SI engine. The study aimed for increasing the performance of SI engine using E25 as mixture of premium-ethanol. The performance of engine was measured by engine test bed on chassis. Change load method is used in the experiment. The experiments result is advancing the time of ignition at 4 degree that can improve the engine performance. The result of changes load use E25 fuel with advanced time of ignition at 4 degree can increase engine performance as torque, power, bmep, efficiency thermal and bsfc were decrease